Impact of corporate governance on related party transactions in family-owned firms in Pakistan - Azim, Fazli; Mustapha, Mohd Zulkhairi; Zainir, Fauzi (Faculty of Economics and Administration, University of Malaya, 2018)
This is an empirical study to examine the impact of corporate governance (CG) variables, namely independent directors index (IDI), family directorship (FD), and family ownership (FO), on the types of related party transactions (RPTs) that prevail in family-owned firms in developing countries. The focus of this study is on Pakistan whereby it was found major shareholders of Pakistani family-owned firms expropriate resources through RPTs. This study analysed panel data of 108 firms of family-owned firms listed on the Karachi stock exchange from 2004 to 2014 after the introduction of CG codes in 2002. The study contributes to literature by categorising all RPTs into three types - RPTb, RPTe, and RPTo. It also develops an index of independence directors comprising three dimensions, namely board composition, financial expertise, and tenure of the independent non-executive director. Different panel least squares models for different RPTs have been employed to examine the relationship between RPTs and CG variables. This study found that 90% of family-owned firms in Pakistan scored low for independent director’s index. Hence, CG is weaker in Pakistani family-owned firms where major shareholders expropriate resources through RPTb and RPTe. Further, CG variables, namely IDI and FD are negatively related to RPTs and the concentration of family ownership of firms has a negative relationship with RPTs, and this has a negative tendency for the resource expropriation of family-owned firms. The study concludes the negative relationship of corporate governance and concentration of major shareholder exploit the interest of minority shareholders in Pakistani family-owned firms.